2014
DOI: 10.1186/s12870-014-0189-3
|View full text |Cite
|
Sign up to set email alerts
|

The pgip family in soybean and three other legume species: evidence for a birth-and-death model of evolution

Abstract: BackgroundPolygalacturonase-inhibiting proteins (PGIPs) are leucine-rich repeat (LRR) plant cell wall glycoproteins involved in plant immunity. They are typically encoded by gene families with a small number of gene copies whose evolutionary origin has been poorly investigated. Here we report the complete characterization of the full complement of the pgip family in soybean (Glycine max [L.] Merr.) and the characterization of the genomic region surrounding the pgip family in four legume species.ResultsBAC clon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 50 publications
0
40
0
Order By: Relevance
“…As suggested previously, these features likely have an adaptive significance for combating more efficiently a broad array of pathogens (Ferrari et al, 2003 ) or responding more rapidly to diverse environmental stimuli (D'Ovidio et al, 2004b ). In support of this view, a recent analysis of the genomic organization and composition of the legume pgip families suggested that the forces driving the evolution of the pgip genes follow the birth-and-death model (Kalunke et al, 2014 ), similarly to what proposed for the evolution of NBS-LRR-type R genes (Michelmore and Meyers, 1998 ). This possibility is based on genomic features that include inferred recent duplications, diversification as well as pseudogenization of pgip copies, as found in soybean, bean, barrel clover and chickpea (Kalunke et al, 2014 ).…”
Section: Pgip Genes and Their Genomic Organizationmentioning
confidence: 80%
See 3 more Smart Citations
“…As suggested previously, these features likely have an adaptive significance for combating more efficiently a broad array of pathogens (Ferrari et al, 2003 ) or responding more rapidly to diverse environmental stimuli (D'Ovidio et al, 2004b ). In support of this view, a recent analysis of the genomic organization and composition of the legume pgip families suggested that the forces driving the evolution of the pgip genes follow the birth-and-death model (Kalunke et al, 2014 ), similarly to what proposed for the evolution of NBS-LRR-type R genes (Michelmore and Meyers, 1998 ). This possibility is based on genomic features that include inferred recent duplications, diversification as well as pseudogenization of pgip copies, as found in soybean, bean, barrel clover and chickpea (Kalunke et al, 2014 ).…”
Section: Pgip Genes and Their Genomic Organizationmentioning
confidence: 80%
“…In support of this view, a recent analysis of the genomic organization and composition of the legume pgip families suggested that the forces driving the evolution of the pgip genes follow the birth-and-death model (Kalunke et al, 2014 ), similarly to what proposed for the evolution of NBS-LRR-type R genes (Michelmore and Meyers, 1998 ). This possibility is based on genomic features that include inferred recent duplications, diversification as well as pseudogenization of pgip copies, as found in soybean, bean, barrel clover and chickpea (Kalunke et al, 2014 ). The organization of the pgip families therefore supports the view that tandem duplications are frequent in stress-related genes and are beneficial for survival in challenging environments (Oh et al, 2012 ).…”
Section: Pgip Genes and Their Genomic Organizationmentioning
confidence: 80%
See 2 more Smart Citations
“…In the soybean (Glycine max), GmPGIP3, which is the most highly expressed gene of this family in the species, is phylogenetically grouped with PvPGIP1 and PvPGIP2, suggesting that the duplication that originated the ancestors of PvPGIP1/PvPGIP2 and PvPGIP3/PvPGIP4 occurred before the separation of Glycine and Phaseolus (Kalunke et al, 2014). Among these genes, PvPGIP2 is the most efficient in inhibiting the largest number of fungal PGs (Manfredini et al, 2005;D'Ovidio et al, 2004bD'Ovidio et al, , 2006.…”
Section: Introductionmentioning
confidence: 99%